2020
DOI: 10.1111/2041-210x.13367
|View full text |Cite
|
Sign up to set email alerts
|

A simple, reliable method for long‐term, in‐stream data logger installation using rock‐climbing hardware

Abstract: 1. Long-term deployment of in-stream data loggers provides valuable information about stream conditions, particularly at times when streams are difficult to sample manually. However, in streams with high water velocities and substantial shear stress, the detachment of loggers from their installation points is a common problem. Thus, successful logger retrieval requires a durable installation method.2. We present a method for data logger installation using rock-climbing hardware that is simple to assemble, econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…For example, whereas our recovery rate with metal housings and stakes was 73% premetal detector, Isaak et al (2013) and Olsen (2013) recovered 84% and 85% of loggers from PVC canisters glued to rocks. Fogg et al (2020) observed an 89% recovery rate when loggers were fastened to boulders with rock climbing hardware for 18 months. Our relatively poor recovery rates with traditional methods of retrieval were not unexpected, given the inconspicuous, low profile of the stake and housing we used.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, whereas our recovery rate with metal housings and stakes was 73% premetal detector, Isaak et al (2013) and Olsen (2013) recovered 84% and 85% of loggers from PVC canisters glued to rocks. Fogg et al (2020) observed an 89% recovery rate when loggers were fastened to boulders with rock climbing hardware for 18 months. Our relatively poor recovery rates with traditional methods of retrieval were not unexpected, given the inconspicuous, low profile of the stake and housing we used.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we constructed a mixed‐effects ordinal regression model wherein the dependent variable was the ordinal response of logger “fate” (1 = recovery with GPS, 2 = recovery with photo, 3 = recovery with metal detector, 4 = no recovery) following the sequence of events during recovery. Because the literature suggests that stream slope (Isaak et al 2013), stream size (Mauger et al 2015), and proximity to areas of human use (Fogg et al 2020) might affect logger recovery, we included as fixed‐effects stream slope (Slope; ft/ft), Strahler stream order (Order), distance to the nearest road (Road; feet), and distance to the nearest incorporated place or population center (Incorp; miles). These four continuous metrics were derived from the National Hydrography Dataset (NHDPlus HR; U.S. Geological Survey) and Topologically Integrated Geographic Encoding and Referencing (TIGER) system (U.S. Census Bureau) using ArcGISPro v2.7 (ESRI, Redlands, California, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations